A Review on the Interconnection Between Drug Design and Controlled Drug Delivery Systems - Mohd. Wasiullah; Piyush Yadav; Amit Pal (Emerging Trends in Personalized Medicines, 2026)
Drug discovery and delivery are two branches of science that have historically developed as independent areas of discovery – one focused on optimizing the properties of molecules for biological activity, and the other on controlling the rate, site, and duration for drug release. However, in contemporary pharmacy, these two areas have merged into a single integrated approach – where drug discovery and delivery strategies co-influence each other at each point of the development process. Rational drug design now considers pharmacokinetic and pharmacodynamic aspects dictated by delivery platforms, while sophisticated controlled drug delivery systems (CDDS) are developed with molecular characteristics in mind, with the goal of optimizing drug action. The purpose of this review is to highlight the relationship between drug design and CDDS, including the main principles and innovations that span the technology, molecular modeling, nanotechnology, and translational aspects that have accompanied the drug design and CDDS relationship. A primary focus is on how the relationship drug design, and CDDS advances toward more precision therapeutics, lowers systemic toxicity, and improves patient compliance. Finally, the state-of-the-art is assessed in terms of the practicality of computational design, more personalized delivery, and adaptive materials toward the drug design and delivery industries as a means of drug innovation.
Keywords: ADMET; Controlled Drug Delivery; artificial intelligence; drug design; molecular modeling; nanotechnology